Tatuaż jako znak przynależności - Wasilewska, Jolanta (Archiwa, Biblioteki i Muzea Kościelne, 2017)
A tattoo is the oldest form of visual individualization, occurring since the dawn of history. Initially, tattoos had protective and ritualistic functions. They differed in respect of social status and religious affi liation. People believed in their curative and magical power. There have been different tattoo techniques depending on the geographic location, material and tools, time, civilization development and tradition. Today’s tattoos are mainly used to decorate the body, but still some people have tattoos done as they are willing to emphasize their belonging to the social group, to commemorate important life events or they are guided by other personal motivations.